Analisis Makna Lirik Lagu "Wie Schön Du Bist" Karya Sarah Connor - Reiza Hardi Mahendra Sinaga; Lydia Purba; Insenalia S.R Hutagalung (Indo-MathEdu Intellectuals Journal, 2023)
A song is an artistic composition of tones or sounds in order, combination, and temporal relationships to produce musical compositions that have unity and continuity. In modern times like this, people only enjoy songs as entertainment. Songs are often sung or heard without knowing the meaning of the lyrics. The song "Wie schön du bist" by Sarah Connor is one of the German pop songs that has meaning in its lyrics. The purpose of this research is to find the denotation meaning, connotation meaning, and myth contained in the lyrics of the song "Wie schön du bist" by Sarah Connor. The method used in this research is descriptive qualitative method, with Roland Barthes semiotic approach to find denotation meaning, connotation meaning, and myth contained in the lyrics of the song "Wie schön du bist" by Sarah Connor. The song "Wie schön du bist" has a meaning that refers to a mother's love for her child. A mother's love for her child cannot be compared to anything in this world. A mother's love can influence a child's growth. A child can also make a mother a place to share her heart.